Competence of Architects in the Context of Jakarta Socio-Cultural-Ecology Architecture - Wijaksono, Sigit; ., Sasmoko; Indrianti, Yasinta; Anindyo Widhoyoko, Samuel (International Journal of Engineering and Technology, 2018)
One city is determined by the characteristics of the urban developing building. The characteristics of the building are determined by the architectural capacity that is influenced by the culture, social and the surrounding environment. In Indonesian cities especially Jakarta, competency standards are needed as a professional detection tool that keeps the legacy of a city of art and building. The problem to be found in this research is how the building of competence that marks a competent architecture for Jakarta. The research method used is exploratory research as one of the stages in Neuroresearch research model. The results of the study found that there are 13 competencies that are able to describe the urban legacy within the architect in the context of the Jakarta Socio Cultural Ecology Architecture.Â Â